Penerapan Model Cooperative Learning Melalui Reward Bintang Untuk Meningkatkan Hasil Belajar Siswa Kelas IX Materi Bangun Ruang Sisi Lengkung di SMP Negeri 3 Kota Bogor - Fitriyani, Aini (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
APPLICATION OF THE COOPERATIVE LEARNING MODEL THROUGH STAR REWARDS TO IMPROVE STUDENT LEARNING OUTCOMES IN GRADE IX THEME BUILDING CURVED SIDED SPACES IN JUNIOR HIGH SCHOOL (SMP NEGERI 3 KOTA BOGOR) Abstract. This research departs from a phenomenon that occurs in class IX of junior high school (SMP Negeri 3 Bogor City) that the low quality of learning Mathematics can have an influence on student learning activities and outcomes. Therefore, a teacher needs to consider learning methods that are appropriate to learning materials so that they can increase student activity and learning outcomes. One of the learning models tested through this research is Cooperative Learning. This study aims to (1) measure student learning activities and outcomes in the material Constructing Curved Sided Spaces Through the Cooperative Learning Model with the Implementation of Star Rewards, (2) knowing the process of increasing student activity and learning outcomes in the Material Constructing Curved Sided Spaces Through the Cooperative Learning Model With The application of the Star Reward, (3) determines the magnitude of the increase in activity and student learning outcomes in the Material of Constructing Curved Side Spaces Through the Cooperative Learning Model with the Application of the Star Reward. The results of this study indicate that the application of the Cooperative Learning Model with the application of star rewards on the Constructed Sides of the Curved Material before applying the learning method has an average value of 54.16. When learning was changed using the Cooperative Learning model with the application of Star Rewards, the average student learning outcomes increased to 74.82 in cycle I and 81.90 in cycle II. It can be concluded that the use of the Cooperative Learning model with the application of star rewards used by teachers can increase the activity and learning outcomes of class IX students of SMP Negeri 3 Kota, therefore the researcher suggests that the application of learning methods needs to be socialized and used in learning Mathematics in schools within the Department Bogor City Education.